Characterization of a Coliphage AS1 isolated from sewage effluent in Pakistan - Ullah,A. (2022)
Abstract The emergence of multi-drug resistant (MDR) bacterial strains, which are posing a global health threat has developed the interest of scientists to use bacteriophages instead of conventional antibiotics therapy. In light of an increased interest in the use of phage as a bacterial control agent, the study aimed to isolate and characterize lytic phages from sewage effluent. During the current study, bacteriophage AS1 was isolated from sewage effluent against E.coli S2. The lytic activity of phageAS1 was limited to E.coli S2 strain showing monovalent behavior. The calculated phage titer was 3.5×109 pfu/ml. PhageAS1 was stable at a wide range of pH and temperature. The maximum stability was recorded at 37ºC and pH 7.0, while showing its normal lytic activity at temperature 60ºC and from pH 5.0 to11.0 respectively. At temperature 70ºC, phage activity was somewhat reduced whereas, further increase in temperature and decrease or increase in pH completely inactivated the phage. From the current study, it was concluded that waste water is a best source for finding bacteriophages against multi-drug resistant bacterial strains and can be used as bacterial control agent.